AC impedance spectroscopy measurement : understanding the effects of 2-, 3-, and 4-electrode cells and cables on experimental data - Lvovich, Vadim (Knovel, 2014)
Electrochemical impedance spectroscopy (EIS) is used extensively for investigating solid oxide and polymer electrolyte fuel cells, batteries, ionic conducting polymers, sensors, and many other specialized applications. This technique has become very popular in investigations of a wide variety of complex electrochemical reactions' kinetics, including corrosion, biomedical fouling, and multistage mass and charge transfer reactions, both in electrolytic solutions and at electrode - electrolyte interfaces. The technique is extensively used for investigating materials with electronic, ionic, or mixed charges.